Chemotherapy-induced neutropenia and febrile neutropenia in patients with gynecologic malignancy. Issue 10 (November 2015) - Hashiguchi, Yasunori; Kasai, Mari; Fukuda, Takeshi; Ichimura, Tomoyuki; Yasui, Tomoyo; Sumi, Toshiyuki
Abstract : Chemotherapy-induced neutropenia is a common complication in cancer treatment. In this study, we investigated chemotherapy-induced neutropenia that was recently detected in all patients with gynecologic malignancy. Between January 2009 and December 2011, we examined cases of chemotherapy-induced neutropenia reported in our hospital. We analyzed the incidence and clinical features of chemotherapy-induced neutropenia and febrile neutropenia in patients with gynecologic malignancy. During the study period, we administered over 1614 infusions (29 regimens) to 291 patients. The median age of the patients was 60 years (range 24–84 years). Chemotherapy-induced neutropenia occurred in 147 (50.5%) patients over 378 (23.4%) chemotherapy cycles. Febrile neutropenia occurred in 20 (6.9%) patients over 25 (1.5%) cycles. The mean duration of neutropenia and fever was 3.6 days (range 1–12 days) and 3.4 days (range 1–9 days), respectively. The source of fever was unexplained by examination or cultures in 14 (56.0%) cycles. There were two cases of neutropenia-related death. Chemotherapy-induced neutropenia was associated with older age (over 70 years) ( P <0.0001), less than five previous chemotherapy cycles ( P =0.02), disseminated disease ( P =0.03), platinum-based regimens ( P <0.0001), taxane-containing regimens ( P <0.0001), and combined therapy ( P <0.0001). Febrile neutropenia was associated with poor performance status ( P <0.0001), no previous chemotherapy ( P <0.05), disseminated disease ( P <0.0001), and distant metastatic disease ( P =0.03). Neither chemotherapy-induced neutropenia nor febrile neutropenia was associated with bone marrow metastases or previous radiotherapy. By identifying risk factors for febrile neutropenia, such as performance status, no previous chemotherapy, disseminated disease, and distant metastatic disease, the safe management of chemotherapy-induced neutropenia may be possible in patients with gynecologic malignancy.